Comparison of four trap types for ambrosia beetles (Coleoptera, Scolytidae) in Brazilian Eucalyptus stands - Flechtmann, C. A.H. [UNESP]; Ottati, A. L.T. [UNESP]; Berisford, C. W. (My University, 2000)
Eucalyptus spp. plantations represent >60% of the reforested area in Brazil. Although ambrosia beetle attacks on live trees were at first nonexistent, they have begun to appear with greater frequency. Monitoring for pest insects is a key factor in integrated pest management, and baited traps are one of the most widely used methods for insect population detection and survey. We compared the efficiency of the most widely used trap in Brazil to survey for ambrosia beetles and other Scolytidae, the ESALQ-84 type, with other traditionally employed traps: the multiple funnel (Lindgren trap); drainpipe; and slot (Theyson) traps, in a Eucalyptus grandis Hill ex Maiden stand in Brazil. The ESALQ-84 trap was the most efficient in trapping Hypothenemus eruditus Westwood and Hypothenemus obscrus (F.); the multiple funnel trap caught significantly more Cryptocarenus diadematus Eggers; whereas the slot trap caught more Premnobius cavipennis Eichhoff and Xyleborus affinis Eichhoff than the other traps. The drainpipe trap was the least effective trap overall. When corrected for number of beetles caught per trap surface area, catches were significantly higher on the ESALQ-84 trap for the majority of the species analyzed, probably because of a smaller trap surface area. The slot trap was recommended for it caught overall more beetles of the three most economically important scolytid species in eucalypt plantations in Brazil, P. cavipennis, X. affinis, and X. ferrugineus. © 2000 Entomological Society of America.
Keywords: Brazil; Trap design; Trap efficiency; Trap surface area; Vertical profile